Melanic and Fulvic Andisols in Volcanic Soils derived from some Volcanoes in West Java - Devnita, Rina (Geological Agency, 2012)
DOI: 10.17014/ijog.v7i4.149Melanic and fulvic Andisols are the great groups in the classification of volcanic soils Andisols, which describe the soils with high organic carbon content in the epipedon. The organic C must be more than 6% in the upper 30 cm with the value and chroma are 2 or less for melanic and more than 2 for fulvic. Melanic epipedon also has to have the melanic index that is 1.70 or less. The objective of this study is to investigate the melanic and fulvic Andisols in volcanic soils that developed under pine forest vegetation (Pinus merkusii) from different parent materials and ages of Mount Tangkuban Parahu (andesitic, Holocene) and Mount Tilu (basaltic, Pleistocene). The method used was a descriptive comparative survey of three profiles in Mount Tangkuban Parahu and three profiles in Mount Tilu. Analyses were done for each horizon in the profiles comprising the investigation of andic soil properties through the analyses of organic C, bulk density, Al + ½ Fe (ammonium oxalate), and P-retention. The investigations were continued by further calculation of organic C content and by investigation of soil colour with Munsell Soil Colour Chart. The results showed that the two profiles in Mount Tangkuban Parahu and two profiles in Mount Tilu are fulvic Andisol. No melanic Andisols were found in both locations. Pine forest vegetation encourages the formation of fulvic Andisols were derived from andesitic-Holocene parent materials or basaltic-Pleistocene parent materials.